WATER TABLE FLUCTUATIONS IN THE RIPARIAN ZONE: COMPARATIVE RESULTS FROM A PAN-EUROPEAN EXPERIMENT - Burt T.P.; Pinay G.; Matheson F.E.; Haycock N.E.; Butturini A.; Clement J.C.; Danielescu S.; Dowrick D.J.; Hefting M.M.; Hillbricht-Ilkowska A.; Maitre V. (My University, 2002)
Soil saturation is known to be of crucial importance to denitrification and other nitrogen cycling processes within the riparian zone. Since denitrification potential generally increases towards the soil surface, water table elevation can control the degree to which nitrate reduction is optimised. Given their topographic location and sedimentary structure, most floodplains are characterised by high water tables. However, detailed field data on water table levels, hydraulic gradients and flow patterns within the riparian zone are generally lacking. This paper presents data collected as part of a pan-European study of nitrate buffer zones, the Nitrogen Control by Landscape Structures in Agricultural Environments project (NICOLAS). An identical experimental design was employed at each site, allowing riparian zone hydrology and nitrogen cycling processes to be explored across a wide range of temperate climates; only the hydrological data are discussed here. A grid of dipwells at 10-metre spacing was installed at each site and manual measurements made at least once a month for a minimum of one year. In addition, at least one dipwell in each grid was monitored continuously using a data logger. All the riparian zones studied displayed a clear annual cycle of water table elevation, although other factors seemed equally important in influencing the range of variation. Where the riparian zone was flat, the water level in the adjoining river or lake proved more significant in controlling water table levels within the riparian zone than was originally anticipated.
Keywords: WATER TABLE; FLOODPLAIN; RIPARIAN ZONE; BUFFER ZONE; NITRATE